Effects of high temperature stress on enzymatic and nonenzymatic antioxidants and proteins in strawberry plants - Gülen, Hatice; Kesici, Müge; Turhan, Ece; İpek, Ahmet; Köksal, Nezihe; Ergin, Sergül (Tubitak Scientific & Technical Research Council Turkey, 2016)
The mechanism of tolerance to high temperatures was investigated in two strawberry (Fragaria x ananassa Duch) cultivars, 'Redlands Hope' ('R. Hope', heat tolerant) and 'Cal. Giant 3' ('CG3', heat sensitive). Leaves were collected from plants that were exposed to gradual heat stress and heat-shock stress separately. The contents of nonenzymatic antioxidants such as ascorbic acid (AsA) and glutathione (GSH) and the activities of enzymatic antioxidants such as ascorbate peroxidase (APX) (EC 1.11.1.11), catalase (CAT) (EC 1.11.1.6), and glutathione reductase (GR) (EC. 1.6.4.2) were measured followed by heat treatments. Additionally, proline content was determined, and heat shock proteins (HSPs) were analyzed with an immunoblotting method to investigate protein markers involved in the heat-stress tolerance of strawberry plants. The contents of AsA and GSH did not change depending on heat stress type, temperatures, or cultivars. While APX and CAT activities increased with high temperatures, GR activity was almost unchanged. The proline content of the cultivars increased in both treatments. Anti-HSP60 immunoblots revealed that a 23 kDa polypeptide was detected during the heat acclimation of strawberry cultivars. The intensity of the heat shock protein in 'R. Hope' plants was more than in 'CG3' plants. Thus, the accumulation of 23 kDa heat shock protein was correlated with the heat tolerance of the cultivars. In conclusion, strawberry leaf tissues of 'R. Hope' were found to enhance the structural stability of cellular membranes under high temperature by increasing both the activity of such enzymes as CAT and APX to activate the antioxidative systems and the expression of 23 kDa HSP.
Keywords: Antioxidative enzyme; Fragaria x ananassa; heat stress; HSP60